ANALISIS PSIKOLOGIS KOMPARATIF PENDEKATAN PEMBELAJARAN KI HADJAR DEWANTARA DAN BENJAMIN S. BLOOM - Idrus L. (Institut Agama Islam Negeri (IAIN) Bone, 2019)
Ki Hadjar Dewantara and Benjamin S. Bloom have different learning approach in term of psychological aspect in learning activities. Ki Hajar Dewantara tends to maximize the potency of each individual i.e. (educate the head, the heart, and the hand) and the social-cultural totality in interacting with the environment with